Pendampingan Literasi Berbasis Digital melalui Komunitas Belajar Baca-Cerdas di Desa Ciptodadi II Kecamatan Sukakarya - M.Syahrun Effendi; Sri Murti; Vella Sabrila Aisah; Riski Yongki Hidayat (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
Based on the results of observations and interviews conducted with a village official, Mr. Feri Ardi Ragil Saputra, the Village Secretary, on July 5, 2024, in Ciptodadi II Village, it was found that the literacy level among the community, especially the youth group, is low. The initial evaluation results showed that literacy skills were categorized as "adequate," with an average percentage of 57.5%, indicating that only slightly more than half of the community has sufficient literacy skills. Meanwhile, the assessment of digital literacy skills showed a low average percentage, with only 15% of participants demonstrating good digital literacy skills, while the rest did not possess adequate digital literacy abilities. However, the final evaluation results indicated a significant improvement. On average, 100% of the indicators were correctly answered. This demonstrates that the digital literacy mentoring activities conducted through the Baca-Cerdas (Smart Reading) community in Ciptodadi II Village, Sukakarya District, were successful in enhancing both reading literacy and digital literacy skills. The expected outcome, as presented in a scientific article to be published in the 2024 edition of the Cemerlang journal, includes the establishment of the Baca-Cerdas learning community as an initiative to improve digital literacy skills among the youth in Ciptodadi II Village, Sukakarya District. Additionally, the program achieved an improvement of over 50% in digital literacy skills among the broader community in Ciptodadi II.